EASTERN THEMES IN WESTERN LITERATURE AND CULTURE - Nizomova Maftuna, M.R.Kilicheva (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The influence and impact of Eastern themes on Western writers has been significant in their literary works. These influences date back to Ancient Rome and continue to span to the present time. Eastern philosophy, religion, folklore, and aesthetics have time and again provided the West with resources to create profound literature. In this article, the focus will be on highlights of impact on Eastern themes on works of famous Western authors and how those elements were appropriated in their work.